The co-ordination of cell division, differentiation and morphogenesis in the shoot apical meristem a perspective - Fleming, Andrew J (Journal of experimental botany, 2006)
Whether morphogenesis is cell division-driven or organismal-based has been a long-running debate in plant biology. This article is a summary of a series of experiments aimed at distinguishing these alternate views by local manipulation of parameters of cell division frequency, orientation, and growth within the shoot apical meristem. These data, put in the context of other investigations in this area, support an organismal view of plant morphogenesis and support the idea that the cell wall plays a key role in the mechanism by which this is achieved. At the same time, the data indicate that the intimate but variable relationship between cell growth and division within the organism means that cell proliferation can indirectly influence this process, leading to a context-dependent influence on morphogenesis. Finally, cell growth and proliferation are intimately related with the process of differentiation as cells exit the meristem. In the final part of the article the molecular mechanism by which these basic cellular parameters are intertwined is discussed